The Essential, Ubiquitous Single-Stranded DNA-Binding Proteins - Oliveira, Marcos T. [UNESP]; Ciesielski, Grzegorz L. (Springer Nature, 2021)
Maintenance of genomes is fundamental for all living organisms. The diverse processes related to genome maintenance entail the management of various intermediate structures, which may be deleterious if unresolved. The most frequent intermediate structures that result from the melting of the DNA duplex are single-stranded (ss) DNA stretches. These are thermodynamically less stable and can spontaneously fold into secondary structures, which may obstruct a variety of genome processes. In addition, ssDNA is more prone to breaking, which may lead to the formation of deletions or DNA degradation. Single-stranded DNA-binding proteins (SSBs) bind and stabilize ssDNA, preventing the abovementioned deleterious consequences and recruiting the appropriate machinery to resolve that intermediate molecule. They are present in all forms of life and are essential for their viability, with very few exceptions. Here we present an introductory chapter to a volume of the Methods in Molecular Biology dedicated to SSBs, in which we provide a general description of SSBs from various taxa.
Keywords: Genome maintenance; Recombination; Repair; Replication; Single-stranded DNA intermediates